2021
DOI: 10.1007/s10100-020-00717-2
|View full text |Cite
|
Sign up to set email alerts
|

The Prisoners’ Dilemma in collaborative carriers’ request selection

Abstract: Logistics providers have to utilize available capacities efficiently in order to cope with increasing competition and desired quality of service. One possibility to reduce idle capacity is to build coalitions with other players on the market. While the willingness to enter such coalitions does exist in the logistics industry, the success of collaborations strongly depends on mutual trust and behavior of participants. Hence, a proper mechanism design, where carriers do not have incentives to deviate from jointl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Multihop routing algorithm and uneven clustering algorithm are the few ways to minimize the hotpot problem [16]. Game [17]- [19] presents the stag hunt game that works effectively in the strategic situations where it just considers random amount of samples, the samples are individuals who are playing a series of stag hunt games tomark their selections in the strategic situation. Game theory acquire confident knowledge from the available data samples [20].…”
Section: Related Workmentioning
confidence: 99%
“…Multihop routing algorithm and uneven clustering algorithm are the few ways to minimize the hotpot problem [16]. Game [17]- [19] presents the stag hunt game that works effectively in the strategic situations where it just considers random amount of samples, the samples are individuals who are playing a series of stag hunt games tomark their selections in the strategic situation. Game theory acquire confident knowledge from the available data samples [20].…”
Section: Related Workmentioning
confidence: 99%
“…Very often, in practical logistics, business players are using different auction systems. In research, Gansterer and Hartl [17] investigate the combinatorial auction system with special attention to the first step of auction where it is necessary that carriers have to decide on the set of requests offered to the auction. Their research shows that a Prisoners' Dilemma can be constructed, but the computational study revealed the opposite.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In [34], with the Braess's paradox's help, losses incurred by the selfish or uncoordinated actions of participants on the transport network are described, known in the literature, as the "price of anarchy." There are numerous studies regarding the price of anarchy in logistics operators proving that rational moves can minimize the price of transport, reducing delivery time and carbon emissions [17][18][19][20][21].…”
Section: Coordinated Use Of the Transport Networkmentioning
confidence: 99%
“…Such problems have been formally modeled in game theory as games with multiple Nash equilibria solutions with equal values [ 5 ]. Tacit coordination problems can be found in real-life situations such as tacit collusion among retail chains [ 6 ], social coordination, allowing, for example, the convergence on a new technological platform [ 7 ], and auction-based collaboration scenarios [ 8 ].…”
Section: Introductionmentioning
confidence: 99%